(untitled) (Research, Society and Development, 2023)
The aim of this project was to raise awareness about the importance of bees and bee products in the context of primary, secondary and higher education (Technology and Degree Courses), located in the municipality of Currais Novos/RN and surrounding municipalities, through a theme room built by graduating students from the previous year (2022), called the Bee and Honey Theme Room (STEAM), consisting of a visual structure, beekeeping and entomological equipment, in order to promote and facilitate learning for the target audience. This action was a continuation of the work carried out previously, in a methodological and cooperative way to develop the environmental, economic and social awareness of students (both from the IFRN Campus Currais Novos, involved in the proposal, as well as other students from other schools), farmers, beekeepers, and the general public interested in beekeeping. At STEAM, through lectures and guided visits, the exchange of experiences took place among related productive sectors (beekeepers, involved family members, and traders). In order to provide more specific training, interactive dynamics took place through thematic workshops, aiming to reach beekeepers and students from IFRN - Campus Currais Novos. Throughout 2023, the Thematic Room reached 765 people in person, including students, education professionals, beekeepers or people with an affinity and interest in this subject. In addition, around 2,600 users were reached via social media. This project therefore achieved its objectives with great success.